Impact of increased access to novel agents on the survival of multiple myeloma patients treated at a single New Zealand centre. Issue 5 (13th May 2019) - Hock, Barry D.; Mulholland, Katie S.; Ganly, Peter; McKenzie, Judith L.; Pearson, John F.; MacPherson, Sean A.
Abstract: Background: The impact of changes in novel agent (NA) usage on the survival of multiple myeloma (MM) patients in real‐world hospital settings is unclear. In New Zealand (NZ) in 2011, frontline bortezomib became available and thalidomide availability was expanded. Aim: This retrospective study analyses the impact these change had on the survival of MM patients treated at a NZ hospital. Methods: Clinical and overall survival (OS) data were collected on MM patients who were treated at Christchurch Hospital during 2000–2009 (pre‐cohort, n = 337) and 2011–2017 (post‐cohort, n = 343). Outcomes were compared using pre‐cohort data truncated at 2011. Results: Patients in the post‐cohort had significant increases ( P < 0.001) in not only NA usage (85 vs 55%) and OS (median = 56 vs 44 months) but also the proportion (74 vs 49%) of young patients (age < 70) who received an autologous stem cell transplant (ASCT). Separate analysis of older patients demonstrated that those in the post‐cohort had significantly longer OS (median OS 28 vs 17, P < 0.001) although 5‐year relative survival remained less than 50%. Separate analysis of young patients demonstrated that those in the post‐cohort had significantly increased initial OS with the survival curves converging at 5 years. Although ASCT‐treated patients had similar OS in each cohort, their progression‐free survival (PFS) was significantly increased in the post‐cohort (median 40 vs 20 months, P < 0.0001). Conclusion: In the setting of a NZ hospital the increased availability of NA was associated with a significant improvement in both the OS of older patients and the PFS of ASCT patients.